2013
DOI: 10.1002/clen.201300353
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Fluoride by Plants: Potential for Phytoremediation

Abstract: Fluoride pollution is now recognized as a global problem. The reason fluorides are considered as serious contaminants even when they are present at low levels is that they persist for a long time in air, soil, and water and exert negative effects at all levels of an ecosystem. Thus, immediate attention is the need of the hour to remediate the environment from F pollution. Till date, the conventional methods have been developed primarily to remove F from water. These methods are very slow and expensive. Besides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 49 publications
2
31
1
Order By: Relevance
“…In case of Chickpea treatment with 1.0 and 2.5 mM NaF showed stimulation in total chl (2.98 and 3.06 mg/g, respectively) over the control. This increase of chlorophyll in presence of F is an exception observation and differs from majority of previous studies in range of species 6 including another cultivar (Anuradha) of C. arietinum. 24 In a study on Triticum aestivum, Tomar et al, 25 reported steady increase in the length of root and shoot and chlorophyll contents by 20 and 40 g/ ml NaF.…”
Section: % Vigor Indexcontrasting
confidence: 99%
See 3 more Smart Citations
“…In case of Chickpea treatment with 1.0 and 2.5 mM NaF showed stimulation in total chl (2.98 and 3.06 mg/g, respectively) over the control. This increase of chlorophyll in presence of F is an exception observation and differs from majority of previous studies in range of species 6 including another cultivar (Anuradha) of C. arietinum. 24 In a study on Triticum aestivum, Tomar et al, 25 reported steady increase in the length of root and shoot and chlorophyll contents by 20 and 40 g/ ml NaF.…”
Section: % Vigor Indexcontrasting
confidence: 99%
“…In a study with fluoride applied (aerially on leaves and systemically via roots) Vicia faba plants, the ability of roots to accumulate higher amount of F than that of the shoot system was noted, which may well explain as to why in our study we found the roots of barley were relatively more tolerant than the shoots (with biomass production of 116.74 and 116.42 mg) at 1.0 and 2.5 mM NaF concentrations, respectively. 23 This fact also conforms to previous observation of relatively high uptake and accumulation of F in both grass and legume species 6 and may account for higher phytotoxicity to root tissues. Changes in the content of photosynthetic pigments in seedlings obtained on various NaF treatments are summarized in Table 3.…”
Section: % Vigor Indexsupporting
confidence: 90%
See 2 more Smart Citations
“…This result means that fluoride damage still persists in this year as well. In fact, fluoride remains for a long time in air, soil and water and exerts negative effects at all levels of an ecosystem (Baunthiyal and Ranghar, 2013). In this respect, a restoration plan to remove those negative effects is needed urgently.…”
Section: Consideration For Restoration Of Ecosystem Damaged By Hf Gasmentioning
confidence: 99%